2022
DOI: 10.3389/fmars.2022.855391
|View full text |Cite
|
Sign up to set email alerts
|

Ecdysis Triggering Hormone, Eclosion Hormone, and Crustacean Cardioactive Peptide Play Essential but Different Roles in the Molting Process of Mud Crab, Scylla paramamosain

Abstract: Molting behavior in insects is controlled by the ecdysis triggering hormone (ETH), eclosion hormone (EH) and the crustacean cardioactive peptide (CCAP). At present, the regulation of molting behavior in crustaceans remains unclear. Here, we studied the roles of ETH, EH, and CCAP in the molt regulation of the crab, Scylla paramamosain from their expression pattern and in vivo assays. The results showed that transcripts of ETH, EH, and CCAP were mainly localized in thoracic ganglia and fluctuated periodically wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 39 publications
0
7
0
Order By: Relevance
“…In the previous study, the expression level of ETH showed a periodic fluctuation with molting, and ETH exists not only at the E stage but also at the other stages ( 18 ). Functional diversity of ETH has been proven in insects (not just triggering ecdysis and working at the E stage) ( 14 16 ).…”
Section: Discussionmentioning
confidence: 79%
See 4 more Smart Citations
“…In the previous study, the expression level of ETH showed a periodic fluctuation with molting, and ETH exists not only at the E stage but also at the other stages ( 18 ). Functional diversity of ETH has been proven in insects (not just triggering ecdysis and working at the E stage) ( 14 16 ).…”
Section: Discussionmentioning
confidence: 79%
“…To balance, the injection of dsETH at the D2 substage led to an increase of ETH when we did sampling for transcriptome analysis. Our previous study showed that ETH was regulated by different models in S. paramamosain , and eclosion hormone was important to the regulation of ETH at the D2 substage ( 18 ).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations